Measurement of dental implant stability by Osstell and Periotest at three different time points: Correlation between the two devices and comparison with clinical characteristics - REYNOLDS, IAN MICHAEL (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2020)
Abstract Measurement of dental implant stability by Osstell and Periotest at three different time points: Correlation between the two devices and comparison with clinical characteristics. Background: Implant stability is a fundamental feature of osseointegration and success of dental implant therapy. Objective and non-invasive measurement devices have been developed to measure implant stability. The purpose of this study was to enhance our understanding of two different implant stability measurement devices, the Osstell mentor and Periotest. Aims: To determine the level of correlation between implant stability measurements of these two devices. To evaluate the influence of a range of clinical characteristics on the values obtained with these measurement devices. To establish a normative range for Zimmer Biomet dental implants with an Osseotite surface. Materials & Methods: A prospective cohort study was undertaken to evaluate stability of dental implants at three different timepoints. Measurements were recorded at implant placement (T1), implant exposure (T2) and implant loading (T3). A range of clinical data was collected including details of the patient demographics, implant surgery, site and fixture features. From September 2018 to July 2020, stability measurements and clinical characteristics were recorded for 29 patients and 68 dental implants at T1, subsequent stability measurements were recorded for 67 implants at T2 and 42 implants at T3. Statistical analysis was performed with IBM SPSS software V26. Data analysis included descriptive statistics and a Spearman?s Rho test to evaluate correlation between values obtained with measurement devices. A Mann-Whitney or Krushal Wallis test was performed to compare stability measurements with clinical characteristic groups. Results: A weak/moderate correlation was observed between mean ISQ and Periotest values at T1, T2 and T3, (r = -0.279, p=0.021), (r = -0.368, p=0.002) and (r = -0.342, p=0.026) respectively. The mean ISQ value was 70.8(SD 7.40) at implant placement, 70.2(SD 8.51) at implant exposure and 72.4(SD 5.42) at implant loading. The mean Periotest value was -3.79 (SD 4.65) at implant placement, -4.60(SD 2.98) at implant exposure and -5.55(SD 2.14) at implant loading. The range of ISQ values observed was 30-89 ISQ at implant placement and 61-82 ISQ at implant loading. The Periotest values ranged from 29 to -8 at 1st stage surgery and -2 to -8 at implant loading. A single dental implant failed shortly after 2nd stage surgery for an overall success rate of 98% during the study timeline. The failed implant had a mean ISQ of 49 and Periotest value of 3 at 2nd stage surgery. There were no radiographic or clinical signs to indicate implant failure at this stage. Conclusions: There is a weak/moderate level of correlation between values recorded with these measurement devices from implant placement to implant loading. For both the Osstell and PeriotestTM a narrowing of stability values is observed from implant placement to fit of prosthesis. The stability values observed in the mandible are higher with the Osstell and lower with the PeriotestTM indicating greater implant stability in the mandible compared to the maxilla. Beyond this finding no clinical characteristic demonstrated a substantial influence on stability measurements of either device. Despite the weak correlation between the values generated by the two devices we would suggest that these devices may be beneficial as adjuncts to standard clinical practice and as instruments that can predict future implant failure. Finally, we propose a normative range of 61-82 ISQ as measured by the Osstell mentor device for osseointegrated Zimmer Biomet dental implants with an Osseotite surface.
APPROVED
Keywords: Implant Stability; Osstell; Periotest